Comment on Dong and Ochsner (2018): "Soil Texture Often Exerts Stronger Influence Than Precipitation on Mesoscale Soil Moisture Patterns". Issue 1 (15th January 2021) - Jakobi, J.; Huisman, J. A.; Bogena, H. R.
Abstract: In their study, Dong and Ochsner (2018, https://doi.org/10.1002/2017WR021692) used an extensive data set of 18 cosmic‐ray neutron rover surveys along a 150 km long transect on unpaved roads to assess the influence of precipitation and soil texture on mesoscale soil moisture patterns. Based on their analysis, they concluded that soil texture, represented by sand content, exerted a stronger influence on mesoscale soil moisture variability than precipitation, represented by the antecedent precipitation index, on 17 of the 18 survey days. However, we found that Dong and Ochsner (2018) made a mistake in their calculation of volumetric soil moisture. After correction, the validity of the original conclusions of Dong and Ochsner (2018) was considerably weakened, as soil texture exerted a stronger influence on soil moisture than precipitation on 12 of the 18 survey days only. Key Points: Dong and Ochsner (2018) concluded that soil texture exerted a stronger influence on mesoscale soil moisture variability than precipitation Dong and Ochsner (2018) made a mistake in their calculation of volumetric soil moisture We found that correlations between soil moisture and soil texture and precipitation were significantly different in only 8 of 18 surveys